The reactivation of somatosensory cortex and behavioral recovery after sensory loss in mature primates - Qi, Hui-Xin; Kaas, Jon H.; Reed, Jamie L. (Frontiers in Systems Neuroscience, 2014)
In our experiments, we removed a major source of activation of somatosensory cortex in mature monkeys by unilaterally sectioning the sensory afferents in the dorsal columns of the spinal cord at a high cervical level. At this level, the ascending branches of tactile afferents from the hand are cut, while other branches of these afferents remain intact to terminate on neurons in the dorsal horn of the spinal cord. Immediately after such a lesion, the monkeys seem relatively unimpaired in locomotion and often use the forelimb, but further inspection reveals that they prefer to use the unaffected hand in reaching for food. In addition, systematic testing indicates that they make more errors in retrieving pieces of food, and start using visual inspection of the rotated hand to confirm the success of the grasping of the food. Such difficulties are not surprising as a complete dorsal column lesion totally deactivates the contralateral hand representation in primary somatosensory cortex (area 3b). However, hand use rapidly improves over the first post-lesion weeks, and much of the hand representational territory in contralateral area 3b is reactivated by inputs from the hand in roughly a normal somatotopic pattern. Quantitative measures of single neuron response properties reveal that reactivated neurons respond to tactile stimulation on the hand with high firing rates and only slightly longer latencies. We conclude that preserved dorsal column afferents after nearly complete lesions contribute to the reactivation of cortex and the recovery of the behavior, but second-order sensory pathways in the spinal cord may also play an important role. Our microelectrode recordings indicate that these preserved first-order, and second-order pathways are initially weak and largely ineffective in activating cortex, but they are potentiated during the recovery process. Therapies that would promote this potentiation could usefully enhance recovery after spinal cord injury.